2013
DOI: 10.1093/gerona/gls253
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Posture in the Sagittal Plane Is Associated With Future Dependence in Activities of Daily Living: A Community-Based Cohort Study of Older Adults in Japan

Abstract: This study indicates that spinal inclination is associated with future dependence in ADL among older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 26 publications
1
22
1
2
Order By: Relevance
“…In their study, Kamitani et al . used a computer‐assisted device for measuring spinal shape, named the Spinal Mouse, and found that spinal inclination in elderly people, but not thoracic curvature, lumber curvature and sacral‐hip angle, was associated with future dependence for ADL …”
Section: Introductioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In their study, Kamitani et al . used a computer‐assisted device for measuring spinal shape, named the Spinal Mouse, and found that spinal inclination in elderly people, but not thoracic curvature, lumber curvature and sacral‐hip angle, was associated with future dependence for ADL …”
Section: Introductioncontrasting
confidence: 81%
“…Trunk inclination was able to be measured with a computer‐assisted device; for example, Spinal Mouse and so on. It was shown that spinal inclination measured with a Spinal Mouse was associated with future dependence of ADL . However, to show the result, we needed to analyze the data with a personal computer and software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we created a composite outcome (dependence in ADLs) using these components. We used this composite outcome in our previous studies . We defined dependence in ADLs as admission to a nursing home (institutionalization) or need of for assistance at home during the follow‐up period, with the latter defined as being deemed eligible for LTC, or confirmed need of for help in any of the six Katz ADL items…”
Section: Methodsmentioning
confidence: 99%
“…Knee joint pain in the previous year was classified into four categories (never, sometimes, often, constant) . All of the above factors have been found and reported to be related to outcomes in the Kurabuchi Study . We previously found that self‐reported hearing loss is associated with future ADL decline, so we treated this impairment as a potential confounder .…”
Section: Methodsmentioning
confidence: 99%